American literature, lynching, and the spectator in the crowd : spectacular violence - Lelekis, Debbie (Lexington Books, 2015)
American Literature, Lynching, and the Spectator in the Crowd: Spectacular Violence examines spectatorship in texts by Theodore Dreiser, Miriam Michelson, Irvin S. Cobb, and Paul Laurence Dunbar. As a figure who is simultaneously within and outside the crowd, the spectator (often in the form of a reporter character) is in a unique position to express the fractures between the individual and the collective in American society, seen most vividly in fictional lynch mob scenes in American literature at the turn of the twentieth century.